Developing Student Creativity Using Mind Mapping Media in Learning Islamic Religious Education - Khoirunnisa, Dinda Suci; Yusuf, Achmad; Yusuf, Wiwin Fachrudin; Ma'ruf, Achmad (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This article discusses the development of student creativity in PAI learning in schools. In the world of education creativity becomes an important thing for students in later days when it is not developed well then will be a negative thing for the students themselves in the future and it becomes a demand to carry out the development of creativity for the mind. With the development of creativity will make students able to compete in the outside world. The purpose of this research is the implementation and process of development of student creativity through mind mapping in Pai learning in students of Class V in Sdn Suwayuwo I. The methods used in this research are R&D methods (Reasearch and Developmen) with the model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Based on the results of the development of creativity students using mind apping there are several processes and stages in the implementation passed so in this study can result in increased creativity and activity of students in PAI learning through mind mapping, in addition students can sharpen the ability to interact between fellow friends both in terms of collaboration of ideas and pemechan problems, as well as students can interact freely about subjects with educators in the given learning. The development of student creativity in learning can be developed through a method, medium or strategy applied in learning through some deeper processes and stages.